Production of powder fish silage from fish market wastes - Hossain, U; Alam, AKMN (SAARC Journal of Agriculture, 2016)
This study was undertaken to investigate the suitability of using fish market wastes (viscera) as raw material for powder fish silage production. Fish viscera contained 14.01±0.68% protein, 20.00±1.04% lipid, 4.75±0.64% ash, 60.62±2.15% moisture and 0.62±0.08% Nitrogen Free Extract (NFE). The pH of fish viscera was 6.21±0.07. For liquid fish silage production, 2, 3, 4 and 5% formic acid were added in blended viscera, of which 4% formic acid was found better that had a pH value of 3.77±0.07. Liquid silage contained 12.00±0.89% protein, 17.26±1.49% lipid, 3.73±0.81% ash, 66.41±3.07% moisture and 0.60±0.09% NFE. For neutralizing liquid fish silage, various concentrations, viz. 1, 2, 3, 4, 5 and 6% Na2CO3 were added. The pH value (6.32±0.01) was better when mixing with 4% Na2CO3. To produce powder fish silage 20, 30, 40 and 50% rice bran were mixed in liquid fish silage. Powder silage made with 30% rice bran was found better to improve the nutritional quality of the product that contained 20.84±0.12% protein, 33.73±0.14% lipid, 14.05±0.27% ash, 10.83±0.19% moisture, 6.61±0.10% crude fiber and 13.94% carbohydrate. The pH value was 6.54±0.01. After preparation, powder fish silage was packaged. The packaged powder fish silage was then stored for 4 months at room temperature (20-300C). After four months of storage, the contents of protein, lipid, ash, moisture, crude fiber, carbohydrate and pH reached at 20.30±0.13, 32.41±0.16, 13.49±0.33, 10.98±0.28, 6.32±0.07, 16.50% and 6.76±0.09, respectively. It was found that nutritional value of powder fish silage was very high and can be used in fish feed to reduce feed cost and enhance aquaculture production. SAARC J. Agri., 13(2): 13-25 (2015)